2005
DOI: 10.1097/01.ta.0000174866.27374.c5
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Circumferential Compression in the Presence of Soft-Tissue Injuries: A Case Report

Abstract: P ulmonary torsion is an uncommon complication of trauma or thoracic operations. 1,2 Increasing surgeon awareness about its existence is important because pulmonary torsion bears significant mortality, which may be decreased if recognized early and treated expeditiously. 1 Pathognomonic radiographic findings exist. 3,4 Spontaneous, pulmonary torsion is a very rare entity with poorly understood etiology. 5,6 In the absence of pulmonary resection, the etiology of pulmonary torsion is unclear and only speculative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 30 publications
0
18
0
2
Order By: Relevance
“…Authors reported a decrease in used units of blood from 17.1 to 4.9 ( p  = 0.0001) in the first 24 h, and from 18.6 to 6 after 48 h in patients treated with external fixation and PB, respectively [42]. However, comparing PB with external pelvic fixation in patients with sacroiliac fractures, Krieg et al found a higher transfusion needs in the first 24 and 48 h in patients who underwent external fixation [43]. …”
Section: Methodsmentioning
confidence: 99%
“…Authors reported a decrease in used units of blood from 17.1 to 4.9 ( p  = 0.0001) in the first 24 h, and from 18.6 to 6 after 48 h in patients treated with external fixation and PB, respectively [42]. However, comparing PB with external pelvic fixation in patients with sacroiliac fractures, Krieg et al found a higher transfusion needs in the first 24 and 48 h in patients who underwent external fixation [43]. …”
Section: Methodsmentioning
confidence: 99%
“…This is an important finding given the feared complication of such devices is soft tissue injury from prolonged use. 25,26 The major strengths of this study are the use of whole fresh cadavers, testing involving real-life simulations of movements, and the use of the Fastrak, three-dimensional motion tracking system. This particular electromagnetic motion analysis can detect angular motion of 0.3 degrees.…”
Section: Discussionmentioning
confidence: 99%
“…There are a few case reports in the literature of this complication 17. A study in healthy volunteers demonstrates that the pressure exerted by some of these devices is close to or even over the level capable of compromising tissue perfusion 16.…”
Section: Methods Of Literature Searchmentioning
confidence: 99%